Analisis experiential marketing terhadap loyalitas pelanggan pada rumah makan ayam penyet di kota Lhokseumawe - Asbar, Yuli; Siregar, Widiana Herawati; Lestari, Silvia Ayu (Jurnal Kajian Manajemen Bisnis, 2020)
Â This study aims to determine the effect of sense, feel, think, act, and relate to customer loyalty at the Ayam Penyet Ulis Restaurant in Lhokseumawe. This research uses quantitative analysis methods that focused on the objectives for generalization. This study uses a correlation model between various questionnaires to consumers and their responses about the effect of experiential marketing on customer loyalty. The sample in this study used accidental sampling. The method of data analysis uses multiple linear analysis. The results of this study indicate that: (1) sense does not have a positive and significant effect on customer loyalty, (2) feel does not have a positive and significant effect on customer loyalty, (3) think does not have a positive and significant effect on customer loyalty, (4) act has a positive and significant effect on customer loyalty, (5) relate does not have a positive and significant effect on customer loyalty at Ayam Penyet Ulis in Lhokseumawe.Keywords: Experiential marketing; customer loyalty